Roman Edessa : Politics and Culture on the Eastern Fringes of the Roman Empire, 114-242 C.E. - Ross, Steven K. (Taylor & Francis Ltd., 2000)
Roman Edessa offers a comprehensive and erudite analysis of the ancient city of Edessa, which constituted a remarkable amalgam of the east and the west.